허혈,재관류 유도 신경세포사멸에 대한 일당귀 물추출물의 신경보호효과 연구 - 오태우; Tae Woo Oh; 박기호; Ki Ho Park; 이미영; Mi Young Lee; 최고야; Go Ya Choi; 박용기; Yong Ki Park (大韓本草學會誌, 2011)
Objectives: The purpose of the study is to determine the neuroprotective effects of the water extract of Angelicae Acutilobae Radix(AA) on ischemia·reperfusion-induced apoptosis in SK-N-SH human brain neuronal cells. Methods: SK-N-SH cells were treated with different concentrations of AA water extract (0.1, 0.2, 0.5 and 1.0 mg/ml) for 2 hr and then stimulated with Dulbecco`s phosphate-buffered saline containing CI-DPBS: 3mM sodium azide and 10 mM 2-deoxy-D-glucose for 45 min, reperfused with growth medium, and incubated for 24 h. Cell viability was determined by WST-1 assay, and ATP/ADP levels were measured by ADP/ATP ratio assay kit. The levels of caspase-3 protein were determined by Western blot and apoptotic body was observed by Hoechst 33258 staining. Results: AA extract significantly inhibited decreasing the cell viability in ischemia-induced SK-N-SH cells. AA also increased the ratio of ADP/ATP in ischemia-induced neuronal cells and decreased the expression levels of apoptotic protein, caspase-3 and apoptotic DNA damage. Conclusions: Our results suggest that AA extract has a neuroprotective property via suppressing the apoptosis and increasing the energy levels in neuronal cells, suggesting that AA extract may has a therapeutic potential in the treatment of ischemic brain injury.